2009
DOI: 10.1115/1.3120305
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Slug Liquid Holdup in Horizontal Pipes

Abstract: Slug liquid holdup is a critical parameter of slug flow, which influences the average liquid holdup and pressure drop along pipelines. The objective of this study is to develop a new correlation to predict slug liquid holdup in horizontal pipes. A large data set with wide ranges of operational, geometrical, and physical property parameters was used to develop the new correlation. The new correlation is a function of one independent mechanistic dimensionless variable, namely, the momentum transfer rate between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Many of these originally published correlations are documented by Pereyra et al [14]. Recently, Al-Safran [15] predicted the slug liquid hold-up based on a single dimensionless variable. He found that the slug liquid hold-up is best correlated with the momentum transfer rate between slug body and the Taylor bubble region.…”
Section: Introductionmentioning
confidence: 82%
“…Many of these originally published correlations are documented by Pereyra et al [14]. Recently, Al-Safran [15] predicted the slug liquid hold-up based on a single dimensionless variable. He found that the slug liquid hold-up is best correlated with the momentum transfer rate between slug body and the Taylor bubble region.…”
Section: Introductionmentioning
confidence: 82%
“…This is because it is usually used to provide a hydrodynamic similarity between different systems [43]. Considering experimental observations in this work and others [54][55][56], ε (L) takes a non-linear form and, hence, the relation between ε (L) and Reynold numbers can be expressed as follows:…”
Section: Correlation Developmentmentioning
confidence: 95%
“…Unfortunately, the program 1. developed in this study for this correlation does not properly match the results of original publication, thus this correlation has not been included in this analysis. Al-Safran [14] study is the only one providing the uncertainty of the slug liquid holdup prediction, which is required for proper design and confidence level analysis. This study quantifies the uncertainty of all the published methods considered.…”
Section: Roumazeilles [21] 1996mentioning
confidence: 99%
“…A large set of data were used to validate the developed correlation Considering the momentum required to accelerate the slow moving liquid film to the slug velocity in the slug front, Al-Safran [14] proposed a semi mechanistic model based on the dimensionless momenttim transfer rate, as follows:…”
Section: Roumazeilles [21] 1996mentioning
confidence: 99%